2015
DOI: 10.1186/s13705-015-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Danger explodes, space implodes: the evolution of the environmental discourse on nuclear waste, 1945–1969

Abstract: Background: The ways in which the public understands nuclear waste affect nuclear waste policy and the actual disposal of nuclear waste. This paper traces the origins and the evolution of the public understanding of nuclear waste through an analysis of a sample of the historical record of the public discourse on the topic. Methods: This paper employs sociocultural anthropology methods innovatively: rather than emphasizing the data collection aspect of participant observation, it emphasizes interpretive discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…They might be less financially constraint. 17 Total capacity takes a significantly negative coefficient. If the share in renewable energy production increases, so does the number of renewable energy policies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They might be less financially constraint. 17 Total capacity takes a significantly negative coefficient. If the share in renewable energy production increases, so does the number of renewable energy policies.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, energy produced by nuclear technology is stable and relatively low in price. Therefore, public awareness and beliefs about possible consequences are heterogeneous across countries and fluctuating over time [16,17]. For instance, Bisconti [18] analyzed long-term public opinion data and concluded that the larger portion of the US public takes a neutral position concerning nuclear energy.…”
Section: Introductionmentioning
confidence: 99%
“…To this researcher, the prompt for addressing the epistemic dimensions of ethnography came with the completion of a project on the sociocultural existence of nuclear waste (Pajo, 2015, 2016). The initial purpose of that effort was to understand anthropologically nuclear waste not in its material existence but in its sociocultural existence and specifically as arising in public discourse in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…So the New York Times is best positioned also for serving as a proxy for the knowledgeable and articulate individual that conventional ethnographic research designates as ‘key informant’. (Pajo, 2015)Systematic interpretive analysis of this de facto ethnographic repository then led to a number of findings and conclusions that are noteworthy and can even be impactful for challenging certain key positions of extant scholarship on the topic (Pajo, 2015; Pajo, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation